Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1158/2159-8290.cd-16-0520
|View full text |Cite
|
Sign up to set email alerts
|

Loss of RasGAP Tumor Suppressors Underlies the Aggressive Nature of Luminal B Breast Cancers

Abstract: Luminal breast cancers are typically estrogen receptor-positive and generally have the best prognosis. However, a subset of luminal tumors, namely luminal B cancers, frequently metastasize and recur. Unfortunately, the causal events that drive their progression are unknown, and therefore it is diffi cult to identify individuals who are likely to relapse and should receive escalated treatment. Here, we identify a bifunctional RasGAP tumor suppressor whose expression is lost in almost 50% of luminal B tumors. Mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 46 publications
4
45
0
Order By: Relevance
“…Ras activation was associated with increased phosphorylation of ERK1/2 and transcripts for Ras target genes and some pathway mediators, but variable rPrl transgene expression and reduced canonical downstream mediators of PRL signaling. These findings coincide with recent reports that elevated Ras signaling drives many clinical luminal B cancers, and is associated with a poor prognosis (Olsen et al, 2017;Wright et al, 2015) . In contrast to Kras-activated tumors, preneoplastic mammary glands maintained constitutive expression of rPrl and displayed elevated transcripts for cytokines associated with pro-tumor myeloid populations.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Ras activation was associated with increased phosphorylation of ERK1/2 and transcripts for Ras target genes and some pathway mediators, but variable rPrl transgene expression and reduced canonical downstream mediators of PRL signaling. These findings coincide with recent reports that elevated Ras signaling drives many clinical luminal B cancers, and is associated with a poor prognosis (Olsen et al, 2017;Wright et al, 2015) . In contrast to Kras-activated tumors, preneoplastic mammary glands maintained constitutive expression of rPrl and displayed elevated transcripts for cytokines associated with pro-tumor myeloid populations.…”
Section: Introductionsupporting
confidence: 92%
“…The low rate of somatic mutations and predicted low tumor infiltrating lymphocytes in NRL-PRL tumors mimic the relative immune silence of clinical luminal breast cancers (Dieci et al, 2016;Luen et al, 2016;Vonderheide et al, 2017) . Although the frequency of RAS mutations is relatively low in human breast cancer (<5%) (Cancer Genome Atlas Network, 2012; Curtis et al, 2012) , recent studies have revealed that a high proportion of luminal B ER+ breast cancers display elevated Ras pathway activity as a result of reduced expression or somatic loss of RasGAP tumor suppressors (Griffith et al, 2018;Olsen et al, 2017;Wright et al, 2015) . RAS itself has been an elusive therapeutic target (McCormick, 2015;Tran et al, 2016) .…”
Section: Discussionmentioning
confidence: 99%
“…These diseases have been notable for the absence of frequent mutations in RAS genes themselves. In prostate cancer, loss of DAB2IP expression leads to coordinated activation of RAS and nuclear factor κB (NF-κB) (Min et al, 2010), whereas in luminal B breast cancers, simultaneous loss of DAB2IP and RASAL2 drives invasion, EMT, and metastasis (Olsen et al, 2016). …”
Section: Ras and Human Diseasementioning
confidence: 99%
“…Moreover, multiple signaling pathways may be required to cooperate at critical steps of metastasis. Transcriptional analysis of different subtypes of breast cancer revealed a specific correlation between the loss of expression of RasGAP tumor suppressor genes and aggressive luminal B breast tumors (Olsen et al, 2017). Functionally, these RasGAP genes cooperatively regulate RAS and NF-kB signaling that enhance metastatic features such as invasion and EMT, respectively.…”
Section: The Transcriptome and Its Regulation Of Metastatic Tumor Cellsmentioning
confidence: 99%